RELATIONSHIP BETWEEN AC AND DC MAGNETIC-PROPERTIES OF A CO-BASED AMORPHOUS ALLOY - LIM, SH; CHOI, YS; NOH, TH; KANG, IK (AMER INST PHYSICS, 1994)
How the ac effective permeability (mu(e)) correlates with dc magnetic properties over a wide frequency range of 1 to 1000 kHz was studied, in an effort to understand the magnetization behavior of the Co-based amorphous alloy of Metglas 2714A subject to an ac magnetic field. In the low-frequency range up to 50 kHz, the correlations between A, and the dc initial permeability, and between mu(e) and the coercivity are found to be good, the correlation coefficient being positive and negative, respectively. No definite correlation is observed with the dc maximum permeability. At high frequencies ranging from about 200 to 1000 kHz, the correlations between A, and the dc maximum permeability, and between mu(e) and the coercivity are observed to be good, the correlation coefficient being negative and positive, respectively. The correlation of mu(e) with the dc initial permeability is poor in this high-frequency range. The correlation with the remanence ratio is found to be rather different from the other three; the ac permeability exhibits a maximum at the value of remanence ratio of 0.5-0.6 at frequencies up to 200 kHz but, at frequencies higher than 500 kHz, it decreases linearly with the remanence ratio. From the correlation results it is considered that the dominant magnetization mechanism is the domain wall motion at frequencies up to 50 kHz and it is spin rotation at frequencies higher than 500 kHz.